2002
DOI: 10.2337/diabetes.51.11.3318
|View full text |Cite
|
Sign up to set email alerts
|

Linkage and Association With Type 1 Diabetes on Chromosome 1q42

Abstract: Type 1 diabetes is a complex disorder with multiple genetic loci and environmental factors contributing to disease etiology. In the current study, a human type 1 diabetes candidate region on chromosome 1q42 was mapped at high marker density in a panel of 616 multiplex type 1 diabetic families. To facilitate the identification and evaluation of candidate genes, a physical map of the 7-cM region surrounding the maximum logarithm of odds (LOD) score (2.46, P = 0.0004) was constructed. Genes were identified in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…In a combined analysis of animal model and human linkage data from a number of autoimmune diseases, chromosome 18q12-q21 demonstrated evidence of linkage, which has now been supported by the analysis of congenic strains in NOD mice (48). There was no support for loci on chromosome 18 at P Ͻ 0.05 in the current study.…”
Section: ϫ5contrasting
confidence: 53%
“…In a combined analysis of animal model and human linkage data from a number of autoimmune diseases, chromosome 18q12-q21 demonstrated evidence of linkage, which has now been supported by the analysis of congenic strains in NOD mice (48). There was no support for loci on chromosome 18 at P Ͻ 0.05 in the current study.…”
Section: ϫ5contrasting
confidence: 53%
“…This region has also been mapped to susceptibility to collagen-induced arthritis (42) and it was linked to murine cerebral malaria (43). Finally, the human equivalent synteny, which lies on distal chromosome 1q, was linked to type 1 diabetes susceptibility (44,45). This region, therefore, seems to be an important one to investigate the genetic basis of autoimmune disorders, notably including type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous genetic studies have shown that defective plasmalogen synthesis associates with impaired membrane trafficking [28] although the implications for type 1 diabetes remain to be established [29]. Plasmalogen synthesis-related genes such as DHAPAT clearly need to be evaluated as potential type 1 diabetes susceptibility genes.…”
Section: Resultsmentioning
confidence: 99%